Detection, Occurrence and Fate of Emerging Contaminants in Agricultural Environments. (1st October 2017) - Snow, Daniel D.; Cassada, David A.; Larsen, Megan L.; Mware, Noelle A.; Li, Xu; D'Alessio, Matteo; Zhang, Yun; Sallach, J. Brett
Abstract : A total of 79 papers published in 2016 were reviewed ranging from detailed descriptions of analytical methods, to fate and occurrence studies, to ecological effects and sampling techniques for a wide variety of emerging contaminants likely to occur in agricultural environments. New methods and studies on veterinary pharmaceuticals, steroids, antibiotic resistance genes, cyanotoxins, and potential effects of biochar use in agricultural environments continue to expand our knowledge base on the occurrence and potential impacts of these compounds. This review is divided into the following sections: Introduction, Analytical Methods, Steroid Hormones, Anthelmintics, Antibiotic Fate and Occurrence, Antibiotic Resistance Genes, Cyanotoxins, and Implications of Biochar in Agricultural Environments.